KAJIAN KOMPOSISI TEMPAT BERBIAK KUMBANG KELAPA (ORYCTES RHINOCEROS L.) TERHADAP LARVA (STUDY ON MATERIAL BREEDING COMPOSITION OF COCONUT BEETLES (ORYCTES RHINOCEROS L.) TO THE LARVAE) - Heriyanto, Heriyanto; Sugihartiningsih, Sri (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2013)
Studies have been conducted in order to determine the composition of materials favored by coconut beetles as a breeding place for the control of larvae by the fungus Metarhizium anisopliae in coconut plantation Sitimulyo village, Piyungan Sub District, Bantul District, from May to November2012.The methode for this research used a complete randomized block design, consist of 5 treatments which were artificial nest coconut beetles lay eggs the size of 0.5cm3 were filled with cow dung, coconut tree powder, market waste, a mixture of cow dung and tree coconut powder, a mixture of cow manure and waste market, each treatment was repeated 4 times.The results showed that the artificial nests containing composition mixture of cow dung and coconut tree powder, beetles the most favored breeding places.